Fine Motor Developmental Delay and Associated Factors among Children Aged 3-5 Years in Surabaya - Elly Dwi Masita; Siti Maimunah (P3M Universitas 'Aisyiyah Surakarta, 2021)
In a preliminary study conducted in March 2018, 60% of children aged 3-5 years had a fine motor developmental delay. This research aims to determine the correlation between birth order, birth spacing, child abuse, religious values, parents' perceptions, educational level, and fine motor developmental delay among children aged 3-5 years. This research was a quantitative analytic with a cross-sectional approach. Sampling used the rule of thumb. Test the analysis applied multiple linear regression with p <0.05. Results: Birth spacing, religious values, parents' perceptions correlated positively with the fine motor developmental delay. While birth order had a negative correlation with fine motor development. There was no association between child abuse, educational level, and the development of fine motor in children.Â Conclusion: there was a correlation between birth order, birth spacing, religious values, parents' perceptions, and fine motor development among children.